ROLE OF HISTORY IN SOCIAL SCIENCE ESPECIALLY IN ECONOMICS - Dr. Hilal Ahmad Parray; Shabir Ahmad Lone (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Economics and history are deeply linked. A historian of any era must have at least a basic understanding of economics because a man's activities in society are intimately tied to economic issues. Economic historians are often in a good position to respond to inquiries regarding current global economic trends and crises because they are able to frame questions about complicated economic, social, and political issues and look for patterns and results of past incidents. The current paper highlights the relation of History in social science especially with Economics and its importance in current scenario.